The Perceptions and Experiences of Nontraditional Students in Teacher Licensure Programs. (January 2023) - Andzik, Natalie R; Baker, Stephanie N.; Koehler, Kristen
Nontraditional students seeking a teaching license are tasked with managing coursework and other responsibilities associated with teacher preparation programs; however, they are also likely navigating family dynamics, financial struggles, and other obligations that traditional undergraduate students do not face. We interviewed 19 preservice teacher candidates and report on their experiences when selecting their university of choice, the barriers they faced, and the supports they received. Participants reported coming to their university because of cost, location, and reputation. They reported common barriers such as inability to work, caring for children, and lack of support or access to other resources. However, participants reported professors and external funding as the major factors that had helped them succeed. Implications about this diverse group of students are discussed.